INOVASI PELAYANAN PEMBAYARAN PAJAK SECARA ELEKTRONIK (E-BILLING) DI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU TAMPAN - Indri Agustia; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Ease, speed, and accuracy in providing a service into service demands in the tax sector, as a concrete step to improve the service quality of the Tax Office Pratama Pekanbaru Charming to make an innovation service tax payment electronically or called e-Billing. However, based on field observations, researchers look at the implementation of this innovation is still a lot of taxpayers who do not understand its use because of the inability to use information technology.The purpose of this research is to find out how innovation of tax service with e-Billing innovation and what factors influencing e-Billing innovation. Theoretical concept used by the researcher is innovation using five indicators that is Relative Advantage, Compability, Complexity, Triability, and Observability This research uses qualitative research method, with descriptive data assessment. In data collection, researchers used interview techniques, observation, documentation, and literature study.The results of this study indicate that the innovation of tax payment with e-billing is done in the Office of Tax Service Pratama Pekanbaru Charming is optimal in accordance with the expected by the taxpayer. Factors affecting the innovation of tax payment with e-billing is the first human resources (apparatus) is the lack of employees in KPP Pratama Pekanbaru Charming, the second Taxpayers who still do not have the willingness to learn to use information technology and still lack understanding of the use of e-billing And the third means (network) Taxpayers are still reluctant to use their own facilities due to the absence of internet network or networking disorders often occur in the gadget so it is feared there will be an error when the data entry taxation.Keywords: Service Innovation, e-Billing